MAPPING OF SCIENTIFIC RESEARCH IN THE AREA OF TEA PUBLISHED IN THE BRAZILIAN JOURNAL OF SPECIAL EDUCATION IN THE PERIOD FROM 2005 TO 2024 (REMUNOM, 2025)
This bibliographic article presents a mapping of Scientific Research (SRs) on Autism Spectrum Disorder (ASD) published in the Brazilian Journal of Special Education (RBEE) from 2005 to 2024. The main objective was to map what has been discussed about ASD in the journal. The methodology used was exploratory, of a bibliographic nature, consisting of the mapping of 73 SRs identified through reading the abstracts. The SR abstracts were analyzed and categorized into thematic focuses and sub-focuses. The results demonstrated a trend of significant growth in the production of research on ASD in the RBEE, especially in periods associated with changes in legislation. A jump from 1% (2005-2009) to 15% (2020-2024) was noted in the proportion of publications on the topic. The most prominent thematic focuses were "Teaching for students with ASD" (23%) and "School inclusion of students with ASD" (22%), indicating a strong focus on pedagogical strategies and integration processes. The conclusions indicate that, despite increased access, challenges persist in retention, participation, and learning, highlighting the need to rethink support strategies and improve teacher training. The study contributes to identifying research gaps, such as the scarce literature on Vocational Education and Youth and Adult Education (EJA) for ASD, and serves as a basis for supporting more effective policies and practices for the inclusion of individuals with ASD.